2005
DOI: 10.1073/pnas.0504767102
|View full text |Cite
|
Sign up to set email alerts
|

Early experience in humans is associated with changes in neuropeptides critical for regulating social behavior

Abstract: The formation of social attachments is a critical component of human relationships. Infants begin to bond to their caregivers from the moment of birth, and these social bonds continue to provide regulatory emotional functions throughout adulthood. It is difficult to examine the interactions between social experience and the biological origins of these complex behaviors because children undergo both brain development and accumulate social experience at the same time. We had a rare opportunity to examine childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
268
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 501 publications
(289 citation statements)
references
References 48 publications
(41 reference statements)
14
268
1
4
Order By: Relevance
“…Both men (Meinlschmidt and Heim, 2007) and women (Riem et al, 2013) show altered responses to intranasal oxytocin after a childhood with significant disruptions in the parent-child relationship. Further, peripheral (urine) oxytocin levels were lower after a social encounter in children with early life histories in institutional settings compared with children who were reared in typical home settings (Wismer Fries et al, 2005). These data in humans suggest that careful attention to experiences in childhood may help disentangle the true nature of the influence of oxytocin and vasopressin system genetics in developing and adult behavior.…”
Section: Gene By Environment Interactionsmentioning
confidence: 76%
“…Both men (Meinlschmidt and Heim, 2007) and women (Riem et al, 2013) show altered responses to intranasal oxytocin after a childhood with significant disruptions in the parent-child relationship. Further, peripheral (urine) oxytocin levels were lower after a social encounter in children with early life histories in institutional settings compared with children who were reared in typical home settings (Wismer Fries et al, 2005). These data in humans suggest that careful attention to experiences in childhood may help disentangle the true nature of the influence of oxytocin and vasopressin system genetics in developing and adult behavior.…”
Section: Gene By Environment Interactionsmentioning
confidence: 76%
“…A mutation may be inherited from parents or occur de novo. On the other hand, prenatal factors (like prenatal stressors [35] and drug abuse [36]) and the postnatal environment (like aberrant social environments [37]) may also lead to alteration of the OXT system, characterized by decreased central OXT mRNA levels and lower plasma OXT levels. Similar to OXT, studies on plasma AVP levels in ASD are limited and the results are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that that the oxytocin system may serve as a critical biological mechanism linking adversity to attachment style. Consistent with this idea, studies have linked childhood mistreatment to lower levels of oxytocin (Heim et al 2009;Wismer Fries et al 2005), and a recent study revealed that methylation (down regulation) of the oxytocin receptor gene mediates the effect of adult stress on changes in attachment style (Simons and Lei 2014). This pattern of results suggests that calibration of the oxytocin system serves to mediate the impact of childhood adversity J Youth Adolescence (2015) 44:573-580 577 on attachment style but that recalibration of this system can take place in adulthood.…”
Section: Implications For the Social Sciencesmentioning
confidence: 92%